Analisis Denyut Nadi Sebelum dan Sesudah Melakukan Lari 12 Menit Mahasiswa Pendidikan Kepelatihan Olahraga Universitas Pejuang Republik Indonesia - Arga, Arga (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze rest, maximum, and recovery pulse rate in students of the Sports Coaching Education Study Program, Pejuang University of the Republic of Indonesia after doing running activities for 12 minutes. This study involved 20 students who measured their resting, maximum, and recovery pulses. The data obtained was analyzed using descriptive statistics to obtain the mean, standard deviation, and variation of each pulse category. The results showed that the average resting pulse was 69.90 bpm with a standard deviation of 2.86 bpm. The maximum pulse rate ranges from 139 bpm to 171 bpm, with an average of 153.35 bpm and a standard deviation of 9.55 bpm. The average recovery pulse was 127.60 bpm with a standard deviation of 5.58 bpm, indicating that students were able to return to a resting state quickly after running. These findings suggest that college students are in good physical condition, indicated by a positive cardiovascular response to physical activity. This research provides the basis for the development of more effective exercise programs and recommendations to increase awareness of the importance of physical fitness among students.